KAPASITAS TAMPUNGAN EMBUNG TRIMULYA TERHADAP KEBUTUHAN AIR IRIGASI DI NAGARI PANYUBARANGAN KABUPATEN DHARMASRAYA SUMATERA BARAT - Nifen, Silta Yulan; Edi, Ventela Isnan Putra (Ensiklopedia of Journal, 2021)
Reservoir Trimulya contained in Jorong Trimulya III Nagari Panyubarangan district Timpeh Kabupaten Dharmasraya. Geographically located at coordinates 0 58’ 17.08’ LS and 101 39’ 39.64’ BT. The location proposed by the society are in the area of plantation source of the water that comes from springs. Proposed plan for the community from the construction of this dam will be used for irrigation of rice fields covering an area of 29 Ha. Layout of the irrigated fields of the plan of the reservoir with the location of the reservoir, the Conditions of irrigation of the rice fields of the existing harness the flow of the springs are directly distributed to the tertiary channels. Reservoir Trimulya is located in the basin area of oil palm plantation with an area DTA 2.1 km2 and area of 4.10 Ha, and the Volume of the Reservoir 178.400 m3. Reservoir Trimulya planned to meet the needs of irrigation in the region Jorong TrimulyaRain average area was calculated using the method of Poygon Thiessen with Sta. the rain effect is the Sta. Padang Sidondang with the availability of data from 2006 – 2020. The average annual rain by 65,54 mm. Water availability is calculated using the Method of Nreca While to discharge the mainstay of using the Method to Method F.J Mock so get the cropping pattern of the annualThe Total irrigation water requirement of rice Fields Trimulya from the results of the calculations have been done of the various phases have been analyzed known to the discharge of Irrigation water requirements,by 3,36 lt/dt/ha. And Estimate the Amount of Water calculated using the Method of Nreca to Reservoir Trimulya with inflow 925.503 m3. And by the Method of F.J Mock Can be Said that the Reservoir Trimulya can meet the needs of irrigated rice fields covering an area of 29 Ha. Cropping Patterns 3 times in 1 Year with the Rice crop, Rice, Rice.